Amplitude analysis of B0s → K0SK±π∓ decays - Aaij, Roel; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; D'Argent, Philippe; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Journal of high energy physics, 2019)
The first untagged decay-time-integrated amplitude analysis of B s 0 → K S 0 K±π∓ decays is performed using a sample corresponding to 3.0 fb−1 of pp collision data recorded with the LHCb detector during 2011 and 2012. The data are described with an amplitude model that contains contributions from the intermediate resonances K*(892)0,+, K 2 * (1430)0,+ and K 0 * (1430)0,+, and their charge conjugates. Measurements of the branching fractions of the decay modes B s 0 → K*(892)±K∓ and B0s→K∗(---)(892)0K0(---)Bs0→K∗(---)(892)0K0(---) B_s^0→ \overset{\left(\hbox{---} \right)}{K^{*}}{(892)}^0\overset{\left(\hbox{---} \right)}{K^0} are in agreement with, and more precise than, previous results. The decays B s 0 → K 0 * (1430)±K∓ and B0s→K∗0(---)(1430)0K0(---)Bs0→K0∗(---)(1430)0K0(---) B_s^0→ \overset{\left(\hbox{---} \right)}{K_0^{*}}{(1430)}^0\overset{\left(\hbox{---} \right)}{K^0} are observed for the first time, each with significance over 10 standard deviations. Open image in new window
Im Titel sind die Plus- und Minuszeichen hochgestellt
Im Titel sind "0" und "S" untereinander geschrieben: "0" hochgestellt, "S" tiefgestellt
Gesehen am 08.08.2019
LHCb collaboration: R Aaij, S. Bachmann, D. Berninghoff, S. Braun, A. Comerma-Montells, P. d’Argent, M. Dziewiecki, D. Gerick, J.P. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, M. Kolpin, R. Kopecna, B. Leverington, H. Malygina, J. Marks, D.S. Mitzel, S. Neubert, A. Piucci, N. Skidmore, M. Stahl, S. Stemmle, U. Uwer, A. Zhelezov [und 821 weitere]